Dimensionality and geometry effects on a quantum carnot engine efficiency - Hiram Kalid Herrera Alcantar; José Carlos Carvajal García; Osvaldo Rosales Pérez; Rubén Cesar Villarreal-Sánchez; Priscilla Elizabeth Iglesias-Vázquez (Revista de Ciencias Tecnológicas, 2019)
We calculate the efficiency of a quantum Carnot cycle for a particle confined in two different infinite potential wells, a cylindrical potential well of variable radius and a two-dimensional square potential well with a periodicity in one of it sides. We find that the efficiency depends directly on the dimensionality and geometry of the well that confined the particle.